Konsep Rahmatan Lil 'Alamin di IAI AL-AZIS Dalam Perspektif Hukum Konstitusi Indonesia - Mutimah Nursabilah Isu; Fathan Al-widad; Toto Jumanta; Ahmad Shofi; Ali Marzuki (STKIP Subang, 2026)
The concept of